PP.06.35: GENDER DIMORPHISM IN THE RELATIONSHIP BETWEEN PULSE PRESSURE AMPLIFICATION AND PULSE WAVE VELOCITY. (June 2015) - Pichler, G.; Martínez, F.; Solaz, E.; Vicente, J.; Calaforra, O.; Pinto, C.; Lozano, J.; Redon, J.
Abstract : Objective: Pulse pressure (PP) amplification reflects pulsatile arterial pressure and is mainly determined by the cardiac output, arterial stiffness (AS) and the returning pulse wave. Pulse wave velocity (PWV) is considered gold standard in the assessment of AS. The aim of the present study was to analyze the difference between genders in the relationship between PP amplification and PWV. Figure. No caption available. Design and method: Patients attending the HTN Unit of the Clinical Hospital of Valencia were included. Central BP was assessed using the SphygmoCor device (Atcor medical, Australia) and PWV was determined using the Complior device (Artech, France). PP amplification was defined as ratio between peripheral and central PP. ANCOVA, partial correlation and multiple linear regression models were used for statistical analysis. Results: 445 patients (50% women; mean age 57.5 ± 11.4 years; 196 hypertensives (44%); 316 (71%) under BP treatment) were involved. PP amplification was higher in men than in women (1.33 and 1.24, respectively, p < 0.001) after adjusting for age, height, HR and PWV. Likewise, PWV was higher in men than in women (9m/s and 8.4m/s respectively, p = 0.003) after adjusting for age, height, HR and PP amplification. PP amplification showed significant correlation with gender and age (r = -0.27 and -0.18, respectively, p < 0.001) as well as with HR and height (r = 0.63, p < 0.001 and 0.1, p = 0.028, respectively). No significant correlation with PWV was found after adjusting for covariates. Main determinants of PP amplification were female sex, age, HR and height (beta = -0.28, -0.18, 0.59, p < 0.001 and beta = 0.12, p = 0.035, respectively). PWV was significantly associated with PP amplification in men (beta = -0.25, p < 0.001), but not in women (beta = -0.04, p = 0.513; p-value for the difference in beta values between gender 0.002; figure). Conclusions: PP amplification and PWV are higher in men than in women. Female sex, age, HR and height are determinants of PP amplification. PP amplification and PWV are inversely associated in men but not in women.